2001
DOI: 10.1034/j.1600-079x.2001.300408.x
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression of the key enzymes of melatonin synthesis in extrapineal tissues of the rat

Abstract: Besides the pineal gland, melatonin is reported to be produced in a number of extrapineal sites, where it could act as an intracellular mediator or paracrine signal in addition to its endocrine effects. In view of the suggested immunoregulatory role of melatonin, we compared lymphoid organs and several other tissues of the rat for their potential to synthesize melatonin. Using the reverse transcription-polymerase chain reaction (RT-PCR) method, we determined the tissue-specific expression of mRNAs encoding two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
133
0
9

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 208 publications
(151 citation statements)
references
References 21 publications
5
133
0
9
Order By: Relevance
“…Nevertheless, in addition to the expected Hiomt expression in goldfish pineal and retina, where MEL synthesis is well documented in vivo and in vitro (Iigo et al, 1991;1997), we found positive signals for HIOMT transcripts in gonads and, to a lesser extent, in liver and gut. These are the first results identifying Hiomt transcripts in non photosensitive organs in fish, and accords with previous studies in rat (Stefulj et al, 2001) and quail (Fu et al, 2001). The high level of gHiomt-2 expression detected in peripheral locations, as gonads, liver, foregut and hindgut support, but do not demonstrate, a local MEL synthesis, and its physiological relevance deserves to be investigated.…”
Section: Distribution Of Aanat-2 and Hiomt-2 Mrna In Goldfishsupporting
confidence: 89%
See 2 more Smart Citations
“…Nevertheless, in addition to the expected Hiomt expression in goldfish pineal and retina, where MEL synthesis is well documented in vivo and in vitro (Iigo et al, 1991;1997), we found positive signals for HIOMT transcripts in gonads and, to a lesser extent, in liver and gut. These are the first results identifying Hiomt transcripts in non photosensitive organs in fish, and accords with previous studies in rat (Stefulj et al, 2001) and quail (Fu et al, 2001). The high level of gHiomt-2 expression detected in peripheral locations, as gonads, liver, foregut and hindgut support, but do not demonstrate, a local MEL synthesis, and its physiological relevance deserves to be investigated.…”
Section: Distribution Of Aanat-2 and Hiomt-2 Mrna In Goldfishsupporting
confidence: 89%
“…One interesting evidences from present results is the peripheral expression of both enzymes, AANAT-2 and HIOMT-2, which supports MEL synthesis in such peripheral locations. Peripheral AANAT expression has been reported in rodents (Gauer et al, 1999: Stefulj et al, 2001, birds (Kato et al, 1999) and frogs (Isorna et al, 2006). Evidences for AANAT-2 expression in fish was reported in rainbow trout peripheral tissues (Fernández-Durán et al, 2007), but not in others species (pike, trout, zebrafish, Bégay et al, 1998;Coon et al, 1998Coon et al, , 1999Gothilf et al, 1999).…”
Section: Distribution Of Aanat-2 and Hiomt-2 Mrna In Goldfishmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the immune system, enzymatic machinery expression involved in melatonin synthesis has been demonstrated in lymphoid organs including thymus (Naranjo et al, 2007), bone marrow Conti et al, 2000), peripheral blood mononuclear leucocytes (Pozo et al, 2004) and in human cultured lymphocytes (Carrillo-Vico et al, 2004). Our results confirmed that all extrapineal tissues studied express both necessary key enzymes for melatonin synthesis, as opposed to Stefulj et al, who showed that neither rat immune system (thymus and spleen) nor other peripheral organs (kidney, liver and heart) contain reliable amounts NAT and/or HIOMT (Stefulj et al, 2001). This discrepancy might be due to a different amplification method used (PCR conventional vs. real time PCR).…”
Section: Discussionsupporting
confidence: 91%
“…Melatonin (N-acetyl-5-methoxytryptamine), a tryptophan derived small indolic molecule, is mainly secreted by the pineal gland locally in several other tissues (4,5). Experimental evidences proposed the diurnal profiles of blood glucose due to melatonin and increased insulin levels in diabetic animals and humans (6).…”
Section: Introductionmentioning
confidence: 99%